La Chronique d’Ernoul : problèmes et méthode d’édition - Massimiliano Gaggero (Perspectives Médiévales)
Ernoul’s Chronicle was transmitted to us through fifty-four manuscripts, which expose several versions of the same text. The previous studies of the relation between those versions were based solely on an incomplete analysis of the literary tradition. This article was written in view of the creation of a new edition of the Chronicle, a project under the direction of P. W. Edbury, and funded by the Arts and Humanities Research Council. The results of the analysis of two textual samples collated on all the manuscripts make it possible for us to present for the first time a stemma codicum able to account for the history of the whole tradition. Moreover, those results allow us to address in a new fashion the problems inherent to the edition of a historical text transmitted to us through several versions.